Balance performance of healthy young individuals in real versus matched virtual environments: a systematic scoping review - Schedler, Simon; Gramann, Klaus; Hill, Mathew W.; Muehlbauer, Thomas (Frontiers in Human Neuroscience, 2024)
Background: Due to technological advancements and the development of consumer-oriented head mounted displays (HMDs), virtual reality (VR) is used in studies on balance performance and balance trainability more and more frequently. Yet, it may be assumed that balance performance is affected by the physical characteristics of the HMD (e.g., weight) and by the virtual visual environment. Moreover, it has been shown that balance is age-dependent with children and adolescents showing worse performances compared to young adults, which may also affect their balance performance in virtual environments. Objectives: The present systematic scoping review aims to provide an overview on the current evidence regarding balance performance of healthy, young individuals (6-30 years) in real and matched virtual environments.A systematic literature search in the electronic databases PubMed, Web of Science, and SPORTDiscus resulted in 9,554 studies potentially eligible for inclusion. Eligibility criteria were: (i) investigation of healthy, young individuals (6-30 years), (ii) balance assessment in the real and a matched virtual environment, (iii) use of a fully immersive HMD, (iv) reporting of at least one balance parameter. Ten studies met the predefined inclusion criteria and were included in this review. All studies were conducted with young adults (19-30 years).Results: Five studies assessed static balance, four studies quantified dynamic balance, and one study measured static and dynamic balance performance. In healthy young adults, static balance performance was similar with and without VR during simple standing tasks (e.g., two-legged stance), but worse in VR during more challenging tasks (e.g., one-legged stance).Concerning dynamic balance, four out of five studies reported worse performance in VR, while one study did not find differences between visual environments. Most importantly, none of the studies investigating healthy youth (6-18 years) met the inclusion criteria.In healthy young adults, balance performance seems to be affected by VR only during challenging static as well as during dynamic balance tasks. The underlying causes remain unclear, but factors such as perceived presence in VR, a shift in sensory organization and/or perceptual distortion may play a role. There is a void in the literature on the influence of VR on balance performance of healthy youth.